“A river with many branches”: song as a response to Afrophobic sentiments and violence in South Africa - Viljoen, Martina (Acta Academica: Critical views on society, culture and politics, 2022)
The purpose of this article is to examine the symbolic role of song regarding Afrophobia in South Africa – a topic which has received limited attention within local music scholarship. To this aim, a textual reading, drawing on thematic analysis serves to identify patterns of cultural meaning represented in “Umshini wami”, as opposed to anti-Afrophobic songs, including Boom Shaka’s “Kwere Kwere” (1993); “Xenophobia” by Maskandi musician Mthandeni (2015), “United we Stand, Divided, we Fall” by Ladysmith Black Mambazo with Malian singer Salif Keita (2015), and “Sinjengomfula” on the CD Tjoon in (2008), a collective production by musicians from Mozambique, South Africa, and Zimbabwe. The question considered is how healing metaphors featured in these songs oppose a politics of fear and the idea of the other as enemy in “Umshini wami”, described in the media as the ‘soundtrack’ of the deadly Afrophobic upsurge of 2008. It is found that, within the context of Afrophobia, the symbolic reach of “Umshini wami” extends beyond inter-racial conflict and in-group black factionalism to convey a politics of ‘war’ on African foreign nationals. Contrastingly, as symbolic exemplifications, healing metaphors in the selection of anti-xenophobic songs discussed speak to a perceived unified identity that, while representing ethnically diverse peoples, may bind Africans together through the fundamental human rights of morality, justice, and dignity.